Adaptive JPEG steganography based on distortion cost updating - Guang-ming TANG; Yi SUN; Xiao-yu XU; Yu WANG (Tongxin xuebao)
Previous adaptive JPEG steganography algorithms mostly calculate image distortion before secret information embedding,so they can’t dynamically adjust distortion costs.Considering the mutual impacts during embedding,an adaptive JPEG steganography algorithm based on distortion cost updating was proposed.Firstly,three factors that affect embedding fluctuations were analyzed,including quantization step,the absolute value of the quantized DCT coefficient to be modified and perturbation error.Then the embedding update strategy (EUS) was proposed,which enabled to dynamically update the distortion costs.After that,an adaptive JPEG steganography algorithm was implemented combining the strategy.The experimental result illustrates that the algorithm can significantly improve the secure performance of JPEG steganography algorithm.